Responding to Teenagers' Emotional Meltdowns: How Outward Bound Instructors Facilitate Development of Anxiety Management Skills. Issue 4 (July 2023) - Larson, Reed W.; Orson, Carolyn N.; McGovern, Gina
Rates of intense anxiety among teenagers have risen dramatically, a major concern. Outward Bound (OB), a wilderness expedition program that promotes learning through challenge experiences, is found to help youth decrease anxiety. To understand how program staff support this learning, we asked 30 OB instructors to describe their successful work with a youth following an intense anxiety episode (a "meltdown"). Using grounded theory analyses we identified eight practices OB instructors employed that facilitated the youth's emotional learning. Examples include: helping them open up to examine their emotions, providing tools for detecting and regulating rising anxiety, and instructor-youth co-planning to manage upcoming anxiety-inducing situations. The analyses also revealed the intentionality in each practice: when it was used, its goals, strategies employed, and how each facilitated youth's active emotional learning. Youth's learning processes across practices evolved from being instructor-initiated to youth-driven. The skills youth learned progressed from understanding emotions, to controlling imminent anxiety, to controlling anxiety about future situations, to taking responsibility for the impact of their emotions on others. These OB practices, we suggest, can be flexibly adapted to other youth development settings to help teens build competencies to manage anxiety, including when taking on new demanding challenges.